Strategies for Developing Teachers’ Competence Through Technology-Based Training in Secondary Schools - Juwairiyah Dahlan; Muzakki Abdurrahman (Al-Qalam Institue, 2024)
This study aims to formulate a strategy for developing teacher competency through technology-based training, relevant to the context of schools adopting the Independent Curriculum. The method used is a qualitative, descriptive-analytical approach, combining literature reviews and analyses of school documents available online, as well as theoretical studies on teacher competency, continuous professional development, and the use of ICT in learning. The results of the study produced several main strategies, namely: (1) designing a tiered technology-based training program; (2) strengthening teachers’ digital competency through the TPACK model; (3) building a professional learning community using an online platform; (4) integrating technology training with Islamic boarding school-based programs; and (5) implementing a continuous monitoring and evaluation mechanism. The implications of this study are expected to serve as a reference for secondary schools, especially those with an Islamic boarding school background, in developing teacher competency to support active, creative, and collaborative learning in accordance with the Pancasila Student Profile.